Persistence of 14 C-Malathion Residues in Stored Milled Rice - Arshad, Juzu Hayati; Mohd Salehuddin, Aini (1988)
The persistence of 14C-malathion residues in milled rice stored for 41 weeks was studied under conditions simulating local practice. Total, surface, extractable and bound residues in the rice grains were determined following a single spraying with the insecticide. After 41 weeks (- 9 months) storage, 10% of the total quantity of the applied 14 C-malathion remained on the surface of the jute sack and 5% was present on the surface and i. side the rice grains. Formation of bound residues was apparently negligible. Data showed also that 50-60% of the total 14 C-malathion residues in the rice were present as surface residues. Washing the rice thoroughly before cooking removed the surface residues. During cooking, 57% of the extractable residues were lost.